Fermented Cheese Whey as a Source of Bioactive Compounds for Gut-Brain Axis Modulation: A Mini Review - Cahyanti, Antonia Nani; Harjanti, Dian Wahyu; Legowo, Anang Mohamad; Rizqiati, Heni (Jurnal Ilmu dan Teknologi Hasil Ternak, 2026)
Cheese whey is a significant dairy by-product, presents an environmental challenge due to its high organic load. However, its rich nutritional profile offers potential for valorization through microbial fermentation. Fermentation of cheese whey has been demonstrated to produce or enhance several bioactive metabolites, such as gamma-aminobutyric acid (GABA), tryptophan, and short-chain fatty acids (SCFAs), which are present in negligible amounts in the unfermented substrate. These metabolites are mechanistically linked to the modulation of the central nervous system and the gut-brain axis. This structured narrative review synthesizes evidence on the fermentation-driven bioconversion pathways responsible for the production of GABA, tryptophan, and SCFAs in whey-based matrices. It also examines the proposed biological pathways, including hypothalamic-pituitary-adrenal (HPA) axis regulation, serotonin-GABA neurotransmitter modulation, and attenuation of gut-brain neuroinflammation, through which these compounds may influence stress-related physiological outcomes. The review further assesses the extent and limitations of current evidence linking these mechanisms to gut-brain-axis health. Reported yields vary significantly across studies and units, with GABA concentrations ranging from 19.55-55.35 mg/100 mL to 365.6 mg/100 mL, most often achieved with supplementation of exogenous glutamic acid or monosodium glutamate, tryptophan concentrations ranging from 12,93-13,87 mg/g protein. These findings suggest that whey fermentation can significantly increase selected neuroactive metabolites under specific strain- and process-dependent conditions, providing biological plausibility for fermented cheese whey as a functional food candidate for gut-brain-axis modulation. However, direct clinical evidence for whole fermented whey products in managing stress-related symptoms remains limited. The findings summarized here should serve as a foundation for standardized production and controlled human trials, rather than as evidence of established therapeutic efficacy.